The Role of Artificial Intelligence in the Strategic Development of a Bank’s Credit Management System - LOBKOО. М.; DUBYNAМ. V.; ZAIETSО. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
Digitalisation of banking institutions’ activities in today’s environment is already an objective reality and is happening regardless of the scale of the banking institution’s operations or its role in the development of the financial services market. All banking institutions are trying to use the potential of digital technologies to improve their work and the quality of the services they provide. First and foremost, these institutions use digital technologies in their own lending activities to improve the efficiency of credit management systems. Among the digital technologies that banks are actively adapting to their activities today, the most promising is artificial intelligence technology, which is currently being implemented by these institutions in their own operational activities. In the article, the role of artificial intelligence technology in the strategic development of the bank’s credit management system is investigated. This is achieved by substantiating the essence of the digital strategy of the banking institution and describing its features. The detailed analysis of the essence of artificial intelligence technology made it possible to build an algorithm for implementing this technology into the credit management system of a banking institution. Within this algorithm, eleven stages have been identified, which will gradually increase the effectiveness of this technology and improve the quality of credit services. Several key approaches were also identified that banking institutions can use when implementing this technology in their activities, namely: centralised, decentralised, and combined. In the article, their essence is considered, and the advantages and disadvantages of their application are highlighted. The detailed analysis of the peculiarities of the digital transformation process of banking institutions, and in particular their credit management systems, as well as the study of the specific features of using the potential of artificial intelligence technology, made it possible to conceptualise the results obtained and substantiate the modern digital model of the bank’s credit management system. This model is gradually being formed and developed by banking institutions in line with the new opportunities offered by digital technologies and the institutions’ own capabilities to use these technologies in their operational activities.